Mathematical Modeling and Analysis of Diesel Hydrodesulfurization Kinetics for Sustainable Environmental Health Solutions - Najat Almabrouk; Alamin Abusbaiha; Najib Meftah; Ruqaia Sheliq (AlQalam Journal of Medical and Applied Sciences, 2025)
Diesel remains a globally essential fuel, especially in transportation, yet its sulfur content poses significant environmental and health risks by forming sulfur oxides (SOx) during combustion. This study presents a mathematical modeling and kinetic analysis of diesel hydrodesulfurization (HDS) as a sustainable solution to produce cleaner fuels. Using catalysts such as Co-Mo/γ-Al₂O₃ in fixed-bed and trickle-bed reactors operating between 300–425°C and 1–20 MPa, the research simulates sulfur removal reactions involving thiophene, benzothiophene (BT), and dibenzothiophene (DBT) present in Libyan crude diesel. Models developed in Polymath and Excel compare kinetic expressions, notably the Langmuir-Hinshelwood-Hougen-Watson (LHHW) and power-law models, with findings indicating that the model corresponding to Equation 2 (Model II) best predicts reactor performance. The study also contrasts HDS with alternative desulfurization methods—such as biodesulfurization, adsorptive, oxidative, and extractive approaches—highlighting HDS’s superior efficiency and refinery compatibility despite challenges in deep desulfurization. Furthermore, the analysis identifies an optimal operating condition at approximately 383°C and 7.33 MPa, balancing catalytic efficiency with durability. Evaluations of catalyst effectiveness and diffusion limitations via the Thiele modulus reinforce the need for optimized catalyst design. Overall, the research underscores the potential of targeted process optimization to enhance sulfur removal, contributing to cleaner diesel fuels and improved environmental health.